The Teacher of Auschwitz : a novel - Holden, Wendy, 1961- (New York, NY : Harper Paperbacks, 2025)
"From the bestselling author of Born Survivors, a novel inspired by the powerful true story of a man who risked everything to protect children in Auschwitz. Fredy built a wall against suffering in their hearts . . . Amid the brutality of the Holocaust, one bright spot shone inside the Nazi death camp of Auschwitz. In the shadows of the smokestacks was a wooden hut where children sang, staged plays, wrote poetry, and learned about the world. Within those four walls, brightly adorned with hand-painted cartoons, the youngest prisoners were kept vermin-free, received better food, and were even taught to imagine having full stomachs and a day without fear. Their guiding light was a twenty-seven-year-old gay, Jewish athlete: Fredy Hirsch. Being a teacher in a brutal concentration camp was no mean feat. Forced to beg senior SS officers for better provisions, Fredy risked his life every day to protect his beloved children from mortal danger. But time was running out for Fredy and the hundreds in his care. Could this kind, compassionate, and brave man find a way to teach them the one lesson they really needed to know: how to survive? The Teacher of Auschwitz shines a light on a truly remarkable individual and tells the inspiring story of how he fought to protect innocence and hope amid depravity and despair"--
Includes bibliographical references.
Keywords: Hirsch, Fredy, -- 1916-1944 -- Fiction; Auschwitz (Concentration camp) -- Fiction; World War, 1939-1945 -- Concentration camps -- Poland -- Fiction; Holocaust, Jewish (1939-1945) -- Poland -- Fiction; Biographical fiction; Historical fiction; Novels